Rapid and robust enzymatic sensing and quantitation of 3, 6-Anhydro-L-galactose in a heterogeneous sugar mixture. (29th June 2017) - Pathiraja, Duleepa; Kim, Kyoung Heon; Choi, In-Geol
Abstract: 3, 6-Anhydro-L-galactose (L-AHG) is a rare sugar found in agar polysaccharides. L-AHG has been used as a bioactive compound over the past few years. While the chromatographic or mass-spectrometric quantitation of L-AHG is quite sensitive and accurate, these methods require a reference standard and an intensive sample preparation procedure. We developed an enzymatic assay for rapid and robust quantitation of L-AHG using anhydrogalactose dehydrogenase cloned from Vibrio sp. EJY3 ( Vej AHGD). Vej AHGD is a NADP + - dependent enzyme which catalyzes the oxidation of L-AHG with a stoichiometric ratio of 1:1. Kinetic characterization of the enzyme showed a Km value of 0.19 ± 0.01 mM. The activity of the enzyme was optimum at 20 °C and pH 8.0. The half-life of enzymatic activity was 12 h under optimum condition. Vej AHGD was highly specific to L-AHG, such that the reaction was not interfered by a variety of mono- or oligo-sugars in a heterogeneous mixture. Except transition metal ions, other cations or chelating agents did not affect the activity of the enzyme. Detection limit of the assay was 0.2 mM at 340 nm in the spectrophotometry. The assay was so rapid to give the result less than 5 min, requiring neither separation nor pretreatment of samples. We suggest application of the assay for detection and quantitation of L-AHG in commercial products and biosensor development. Graphical abstract: Highlights: A novel anhydrogalactose dehydrogenase was characterized for bioassay. Rapid and robust enzymatic assay of 3, 6-Anhydro-L-galactose was developed. The assay is highly specific and undisturbed by a heterogeneous sugar mixture. The detection limit of enzymatic assay is 0.2 mM.